Influence of Transformational Leadership on Knowledge Hiding: Mediating role of Organizational Psychological Ownership: A Propose Framework - Ladan, Sahnun; Nordin, Norani; M., Belal H. (2017)
Purpose: Research on knowledge hiding behaviour among employees in organizational is still in its infancy and remain scarce despite its prevalence and negative impact as reported by previous studies.Some of the possible suggested antecedents of knowledge hiding studied include trust, job characteristic, organizational culture, and work environment.Despite these studies, few have attempted to investigate the influence of transformational leadership on knowledge hiding behaviour.Furthermore, the mechanisms through which transformational leadership influences on knowledge hiding behaviour in organizations are not adequately investigated. Therefore, mediator variable is proposed.Findings: Based on transformational leadership theory and psychological ownership theory, this paper proposes that the relationship between transformational leadership and knowledge hiding behaviour of employees in the organization could be mediated by organizational psychological ownership.Implications: Thereby the organization would contain employees that are motivated and behave positively towards organizational performance.